Enzymatic Activities of Bok Choy (Brassica rapa subsp. Chinensis) Grown Soil with the Amendment of Sandwich Compost - Chooi Lin Phooi; Elisa Azura Azman; Roslan Ismail (International Journal of Agronomy)
Soil enzymes ensure our food security, yet they are vulnerable to abiotic stresses. Solving the global issues of food waste by amending the Sandwich compost can be a great solution to ensure food security. Food waste Sandwich compost substrate (as soil amendment) and leachate (as seed priming solution and liquid fertilizer) were used to grow Bok Choy for 4 growing cycles, where soil pH, cation exchangeable capacity, moisture content, aggregate stability, and enzyme activity were determined. The Sandwich compost substrate amendment increased soil pH close to neutral and CEC up to 1.5-fold. Anaerobic Sandwich compost substrate-amended soil reduced soil catalase activity. Still, it steadily increased during the growing cycle. The Sandwich compost substrate amendment soil sustained the aggregate stability for 4 growing cycles. On the flip side, aggregate stability without the Sandwich compost substrate amended soil declined from the growing cycle to the next growing cycle. All variables were positively correlated except catalase activity. Henceforward, Sandwich compost substrate is recommended to improve soil quality in the aspects of pH, CEC urease activity, and dehydrogenase activity.